CH4 transport in wetland plants under controlled environmental conditions : separating the impacts of phenology from environmental variables - Ge, Mengyu; Korrensalo, Aino; Putkinen, Anuliina; Laiho, Raija; Kohl, Lukas; Pihlatie, Mari; Lohila, Annalea; Makiranta, Päivi; Siljanen, Henri; Tuittila, Eeva-Stiina; Wang, Jinsong; Koskinen, Markku (Springer Nature, 2025)
Background and Aims Methane (CH4) fluxes at peatland plant surfaces are net results of transport of soil-produced CH4 and within-plant CH4 production and consumption, yet factors and processes controlling these fluxes remain unclear. We aimed to assess the effects of seasonality, environmental variables, and CH4 cycling microbes on CH4 fluxes from characteristic fen species. Methods Four species (Carex rostrata, Menyanthes trifoliata, Betula nana, Salix lapponum) were selected, and their CH4 fluxes determined in climate-controlled environments with three mesocosms per growing season per species. Microbial genes for CH4 cycling were analysed to check the potential for within-plant CH4 production and oxidation. Two extra experiments were conducted: removal of C. rostrata leaves to identify how leaves constrain CH4 transport, and a labelling experiment with S. lapponum to distinguish between plant-produced and soil-produced CH4 in the plant flux. Results All species showed seasonal variability in CH4 fluxes. Higher porewater CH4 concentration increased fluxes from C. rostrata and M. trifoliata, decreased fluxes from S. lapponum, and did not affect fluxes from B. nana. Air temperature only and negatively affected CH4 flux from C. rostrata. Light level did not impact CH4 fluxes. Both methanogens and methanotrophs were detected in shoots of S. lapponum and M. trifoliata, methanotrophs in B. nana, and neither in C. rostrata. Conclusion Our study demonstrates that the seasonal phase of the plants regulates the CH4 fluxes they mediate across species. The detection of methanogens and methanotrophs in herbs and shrubs suggests that microbial processes may contribute to their CH4 fluxes.
Keywords: metaani; suokasvillisuus; suot; metanogeenit; metanotrofit; sarat; varvut